Pecha Kucha with Part-Task Training Improves Airway Management in Fresh Frozen Cadavers: A Case-Control Observational Study - (:unkn) unknown (KARGER, 2020)
Objective: The objective of this study was to ascertain whether the addition of part-task training as a step in Pecha Kucha for fiberoptic tracheal intubation increases the success rate and reduces the complication rate. Subjects and Methods: The residents of the Department of Anesthesiology were initially included in an orientation program. We used the Pecha Kucha method for the presentation of teaching fiberoptic intubation skills. Afterwards the participants were trained in Laerdal (R) airway management and each participant performed tracheal intubation using the Aintree catheter. The participants were divided into two groups. Group 1 (n = 9) received part-task training and group 2 (n = 9) received whole-task training. The tracheal intubation performances of participants were evaluated on fresh frozen cadavers. The number of interventions, incidence of complications, success rate, and optimization maneuver requirements were recorded. Results: Eighteen residents aged between 27 and 33 years were included. All were junior residents with less than 2 years of experience. There was no significant difference in terms of duration of tracheal intubation, complication rates, and optimization maneuvers between the study groups. Six participants could not place the tracheal tube in the last section. The success rates for the part-task group during Aintree and tracheal tube placement were 100 and 66.7%, respectively, whereas the rates were 55.6 and 44.4%, respectively, in whole-task group (p < 0.05). Conclusion: In addition to the Pecha Kucha method in fiberoptic intubation training, simulation-based part-task training appears to increase the success rate and to reduce the complication rate on fresh frozen cadavers.
Keywords: Airway management education; Pecha Kucha; Anesthesiology; INTUBATION; GUIDELINES; FIDELITY; SKILLS